The State of Law and Democracy: History of Development and Challenges in Indonesia - Maskawati Maskawati; Muhammad Tryas Budi Firamulia; Burhanuddin Burhanuddin (Law and Justice research journal, 2025)
The state of law and democracy are two concepts that are interrelated in the mechanism of managing the government of a country. Democracy provides the foundation for creating equality and equality of rights for all citizens, while the state of law emphasizes that power in a country must be subject to the rule of law, not the will of a particular individual or group. This research is a normative legal research with a normative juridical approach that seeks to explore the harmony of legal rules with applicable norms. The results of the study show that from the colonial period to the reform era, a lot of progress has been made in strengthening the principles of the rule of law, both formally and substantially. The 1998 reform was a momentum that marked a strong commitment to make Indonesia a democratic country of law, where every citizen has rights and obligations protected by law. In Indonesia, democracy has gone through various phases from the parliamentary era, Guided Democracy, New Order, to the reform era that provides greater space for people's involvement.